Environmental Factors Moderate Glyphosate-induced Antagonism of POST Herbicides on the Rapid Response Biotype of Glyphosate-Resistant Giant Ragweed (Ambrosia trifida). Issue 3 (8th January 2018) - Harre, Nick T.; Young, Julie M.; Young, Bryan G.
Abstract: In the rapid response (RR) biotype of glyphosate-resistant (GR) giant ragweed ( Ambrosia trifida L.), exposure to glyphosate elicits H2 O2 production in mature leaves, resulting in foliage loss and reduced glyphosate translocation. When glyphosate is applied with POST herbicides intended to improve control of A. trifida, the RR to glyphosate has the propensity to antagonize these herbicide combinations. This research documents how transient changes in air temperature, soil moisture, and light intensity during a 6-d period surrounding herbicide application regulate induction of the RR and the effect on POST herbicide interactions with glyphosate. Air temperature had the greatest influence on H2 O2 accumulation in leaf disks following treatment with glyphosate, as plants at 30 C produced more than twice the amount of H2 O2 at 2.5 h after treatment compared with 10 C. Plants under field capacity conditions accumulated nearly 50% more H2 O2 than those at one-third field capacity, while those under no shade had only 18% more H2 O2 compared with those in a shaded environment. Despite these initial results, dry weight reduction at 21 d after treatment never differed by more than 8% between levels of environmental factors, thus indicating a negligible influence on glyphosate efficacy. The magnitude of glyphosate-induced antagonism was generally greater at 30 C (12% to 21% less than expected control) versus 10 C (11% to 16%) on atrazine, cloransulam, dicamba, and topramezone and was greater at field capacity (20% to 24%) versus one-third field capacity (11% to 15%) on cloransulam and topramezone. These results indicate air temperatures and soil moisture levels conducive to optimal plant growth accelerate the RR to glyphosate, thereby increasing the likelihood of glyphosate-induced antagonism on several translocated herbicides.